Making the case for virtual competency-based education: Building a twenty-first century small business workforce. Issue 1 (25th June 2020) - Cates, Steven Vaughn; Doyle, Sean; Gallagher, Lisa; Shelton, Gary; Broman, Noel; Escudier, Blake
Abstract : Purpose: The purpose of this paper is to present a competency-based curriculum design model based on a set of ten foundational professional competencies (PCs) that prepare college graduates to meet the needs of global businesses now and in the future. Design/methodology/approach: This phenomenological single-case study reviews literature on the foundational principles of competency-based education (CBE) and comparatively analyzes the results of qualitative interviews to create a set of ten PCs linking employee and business success. Findings: This study presents a theoretical competency-based curriculum model (competency-based learning, performance and behavior (CBLPB)) designed for online education programs to enable a twenty-first century workforce to succeed. The curriculum design model is tested as applied by the researchers in various courses taught at an online university. Research limitations/implications: This is a conceptual model for testing in academic research settings in colleges and universities. Practical implications: The study suggests that higher education business curriculum should be designed using a CBE model to develop graduates with the foundational PCs that employers need and desire in educated working professionals. Originality/value: From the faculty perspective, the CBLPB curriculum design model can enhance the design and implementation of CBE in business programs.